2019
DOI: 10.1371/journal.pone.0220282
|View full text |Cite
|
Sign up to set email alerts
|

Thinking in action: Need for Cognition predicts Self-Control together with Action Orientation

Abstract: Need for Cognition describes relatively stable interindividual differences in cognitive motivation. Previous research has shown relations of Need for Cognition to Self-Control–a capacity that can be broadly defined as resistance to temptation–yet, the processes underlying this relation remain unclear. One explanation for the prediction of Self-Control by Need for Cognition can be an increased motivation to invest cognitive effort with higher levels of Need for Cognition. Another possible link could be that ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 64 publications
(195 reference statements)
7
46
1
Order By: Relevance
“…Although there are some studies that investigated the relationship between NFC and self‐control (Bertrams & Dickhäuser, 2009, 2012b; Grass et al., 2018; Grass, Krieger, et al., 2019; Nishiguchi et al., 2016), hardly any study examined the relationship between NFC and inhibitory control or other EF. One study investigated correlations of NFC with performance in the Stroop task and found no correlation with mean reaction times in interference trials when administering a Stroop task without a previous depleting task (Bertrams & Dickhäuser, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some studies that investigated the relationship between NFC and self‐control (Bertrams & Dickhäuser, 2009, 2012b; Grass et al., 2018; Grass, Krieger, et al., 2019; Nishiguchi et al., 2016), hardly any study examined the relationship between NFC and inhibitory control or other EF. One study investigated correlations of NFC with performance in the Stroop task and found no correlation with mean reaction times in interference trials when administering a Stroop task without a previous depleting task (Bertrams & Dickhäuser, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Given the conceptual overlap concerning effort investment, there have been empirical efforts to relate NFC to Self-Control that typically yielded correlations of r = .30 –.40 [ 24 27 ]. In one of these studies that preceded the present one, we also aimed to relate both constructs more systematically to each other and to establish a hierarchical factor model.…”
Section: Introductionmentioning
confidence: 99%
“…On a cognitive level, effortful control is highly related to executive functions, especially to updating and monitoring processes in working memory (Bridgett et al, 2013). Finally, self-control and effortful control are strongly correlated and load on a common self-control factor (Grass et al, 2019). In summary, we postulate that there are two main clusters having an impact on cognitive effort investment: The first refers to dimensions associated with cognitive motivation, i.e., NFC and intellect.…”
Section: Introductionmentioning
confidence: 87%